Legal Liability By Organs of Social and Humanitarian Foundations Against Misuse of Foundation Funds - Muhammad Iqbal Maulana; Grasia Kurniati; Rani Apriani (Universitas Widya Gama Malang, 2023)
Foundation is a legal entity that is functionally a means to carry out social activities which was established with the intention of improving the welfare of others and not for commercial purposes or for profit. A foundation as a legal entity has its own assets that are separate from the assets of its management. The foundation's source of funds can come from donations or donations from third parties or from business activities carried out by the Foundation. Where the wealth is used to carry out its activities, besides that the foundation also requires funds to meet its operational needs for the sustainability of the foundation. However, recently there have been findings related to the organs of social and humanitarian foundations that deviate by misusing the assets of the foundation. This is a result of the lack of public supervision related to the foundation so that there is a deviation from the aims and objectives of the foundation. This study was conducted to find answers to the formulation of the problem regarding the role and authority of the foundation organs and how the legal accountability of the foundation organs for the misuse of foundation funds. The research method used in normative juridical research, the data used is secondary data in the form of primary legal material which comes from Law Number 16 of 2001 concerning the Jo Foundation. Law Number 28 of 2004 concerning Amendments to Law Number 16 of 2001 concerning Foundations. and secondary legal materials related to this research. The results of this study are to find out related to the duties, functions and authorities of foundation organs in accordance with the Foundation Law and also how the legal accountability of foundation organs for misuse of foundation funds.